Maximizing Energy Content and CO2 Bio-fixation Efficiency of an Indigenous Isolated Microalga Parachlorella kessleri HY-6 Through Nutrient Optimization and Water Recycling During Cultivation - Farooq, Wasif (Frontiers in Bioengineering and Biotechnology, 2022)
An alternative source of energy and materials with low negative environmental impacts is essential for a sustainable future. Microalgae is a promising candidate in this aspect. The focus of this study is to optimize the supply of nitrogen and carbon dioxide during the cultivation of locally isolated strain Parachlorella kessleri HY-6. This study focuses on optimizing nitrogen and CO2 supply based on total biomass and biomass per unit amount of nitrogen and CO2. Total biomass increased from 1. 23 ~ 2.3 g/L with an increase in nitrogen concentration from 15.8 mg/L to 47.4 mg/L. However, biomass per unit amount of nitrogen supplied was higher at low nitrogen content. Biomass and CO2 fixation rate increased at higher CO2 concentrations in bubbling air, but CO2 fixation efficiency decreased drastically. Finally, the energy content of biomass increased with both increases in nitrogen and CO2 supply. This work thoroughly analyzed the biomass composition via ultimate, proximate, and biochemical analysis. Water is recycled three times for cultivation at three different nitrogen levels. Microalgae biomass increased during the 2nd recycled and then decreased drastically during the 3rd. Activated carbon helped remove the organics after 3rd recycled to improve the water recyclability. This study highlights the importance of selecting appropriate variables for optimization by considering net energy investment in terms of nutrients (as nitrogen) and CO2 fixation efficiency and effective water recycling.